Volume 2: A Statistical Report on Waves 1 to 4 of the HILDA Survey - Warren, D; Headey, B (My University, 2007)
The Statistical Report is based on the first four waves of data collected by the HILDA Survey. It contains short articles that provide an annual update of changes in key aspects of life in Australia, covering the four main areas of HILDA, namely: Households and family life; Incomes and economic wellbeing; Labour market outcomes; and Life satisfaction, health and wellbeing.
Families, Incomes and Jobs
Keywords: Families and relationships; Health and wellbeing; Labour market; Health and wellbeing; Employment and unemployment; Families and relationships